Pre-competitive emotions in team sports: Differences across gender and perceived importance and difficulty of the competition - Dias, C.; Cruz, J. F.; Fonseca. A. M. (Revista Portuguesa de Ciências do Desporto, 2014)
The purpose of the present study was to analyse precompetitive emotions in team sports, assessing differences between athletes from different genders, and with different perceptions regarding the importance and difficulty of the competition. Fifty-four athletes (n = 30 female, n = 24 male, M = 22.76 years, SD = 4.42) completed the Portuguese version of the Competitive State Anxiety Inventory-2, and an Inventory of Emotions in Sport. Results showed that participants experienced positive emotions (e.g., hope, happiness) more intensely than negative emotions (e.g., guilt, shame). Additionally, significant positive correlations were found between the positive emotions and self-confidence. Finally, athletes who perceived the competition as more important and difficult reported significantly higher levels of hope and anxiety. These results lend support for further investigation into different positive and negative emotions in sport, as well as their interaction with individual and situational variables.